2011
DOI: 10.3390/s110202177
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic and LIDAR Sensors for Electronic Canopy Characterization in Vineyards: Advances to Improve Pesticide Application Methods

Abstract: Canopy characterization is a key factor to improve pesticide application methods in tree crops and vineyards. Development of quick, easy and efficient methods to determine the fundamental parameters used to characterize canopy structure is thus an important need. In this research the use of ultrasonic and LIDAR sensors have been compared with the traditional manual and destructive canopy measurement procedure. For both methods the values of key parameters such as crop height, crop width, crop volume or leaf ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
135
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 28 publications
5
135
0
4
Order By: Relevance
“…Terrestrial lidar has been successfully implemented to explore biophysical properties of vines [9][10][11][12][13]. Keightley et al [10] measured uprooted grapevine trunk biomass with a stationary terrestrial lidar scanner.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial lidar has been successfully implemented to explore biophysical properties of vines [9][10][11][12][13]. Keightley et al [10] measured uprooted grapevine trunk biomass with a stationary terrestrial lidar scanner.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been increasingly used in field phenotyping [26]. Llorens et al [30] compared the use of ultrasonic sensors and LiDAR to capture canopy characterization in vineyards, and they concluded that data obtained with LiDAR is generally more precise than data obtained with ultrasonic sensors. Rosell Polo et al [31] designed a tractor-mounted LiDAR to scan several kinds of tree and plantations from the side view.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study cannot confirm directly this thesis. Studies on other crops (Walklate et al, 2003;Dammer et al, 2008;Llorens et al, 2011), including potato (Cooke et al, 2011) indicate that crop and canopy characteristics modify the fungicide rate per leaf surface area unit and could affect fungicide efficiency.…”
Section: Fungicide Dose Responsementioning
confidence: 99%
“…Due to physical and mechanical process it can cause disappearance, dispersing and redistributing of active ingredients by volume and intensity of rainfall (Bruhn & Fry, 1982b;Töfoli et al, 2014). Töfoli et al (2014) showed that systemic, including azoxystrobin, or inherent tenacity fungicides were less affected by the simulated rainfall than contact fungicides against P. infestans and Alternaria solani on potato leaf. Chlorothalonil gave a very similar result to azoxystrobin when rain was simulated 0.5, 1 and 2 hours after application against A. solani.…”
Section: Introductionmentioning
confidence: 99%